Nursing care toward older adults with dementia: An integrative review. Issue 1 (9th March 2021) - Adolfo, Cris S.; Albougami, Abdulrhman Saad B.; Roque, Mark Y.; Almazan, Joseph U.
Abstract: Background: Dementia among older adults is receiving increase attention due to its neurodegenerative pathologies and poses a significant challenge for healthcare services systems. Caring for older adults with dementia is frequently challenging. This integrative review appraised and synthesised the existing literature describing the nursing care given to older adults with dementia. Methods: An integrative review was used using six electronic databases (CINAHL, Medline, Science direct‐Elsevier, Proquest, Pubmed and Web of Science). The search terms that were included in various combinations using mesh terms were as follows: nurse* OR nursing staff* AND caring OR care OR caring behavior OR affectionate OR compassionate AND older person* OR aging* OR elder* OR geriatric patient* OR older adult* OR gerontology* OR aged* OR old age. A standardised review by Kmet et al. instrument was utilised for appraising the quality of selected 13 articles. Results: The results were presented based on the two major themes: challenges in providing care and identifying and managing older adults' difficult behaviours. Conclusion: The findings of an integrative review can be used as a foundation for formulating recommendations for how dementia care by nurses can be improved and highlighting where policy development and further research are needed.